Relationship between Bank Credit and Economic Growth: Evidence from Nepal - Adhikari, Gyan Mani; Mahara, Tilak Singh; Dahal, Jyoti (NCC Journal, 2024)
Bank credit serves as the lifeblood of economic activities. The paper aims to investigate how bank credit contributes to economic growth by employing the ARDL model, spanning the period 1975 to 2023 in Nepal. The observed empirical analysis shows a positive short-run and long-run association between bank credit and the growth in the economy. The findings of the study suggested that policymakers should focus on increasing credit by the banking and financial sectors to boost economic growth in the long run.